Metal-based drugs. (1st March 2014) - McQuitty, Ruth
Metals have been considered for millennia to have medicinal values. With the advent of modern medicine, many metal-based drugs have proven to be highly effective in the clinic. Many different metal ions have shown activity against a range of diseases. The unique electronic structure of transition metals offers great versatility, not always seen in organic drugs, in terms of the ability to tune the properties of a given molecule. This review gives a brief overview of the most established therapeutic metals, and their more common applications, such as platinum-based anticancer drugs. New developments within the field of metallodrugs and novel strategies being employed to improve methods of delivery, are also discussed.